The Impact of CEO Education and Board Diversity on Innovation: Focus on Fintech Companies in Indonesia - Kurniawan Kurniawan; Noorlailie Soewarno (AKRUAL: JURNAL AKUNTANSI, 2026)
Research Background: As fintech opportunities continue to grow in Indonesia, CEOs face substantial challenges in establishing public trust and implementing strategic innovations. In this context, the CEO plays a central role in driving technological innovation to improve service quality and user accessibility. Introduction / Main Objectives: This study examines the influence of CEO educational background and board diversity on corporate innovation in Indonesian fintech companies. Method: Using secondary data collected from company websites and the Indonesia Stock Exchange (IDX) between 2015 and 2019, this study investigates how educational qualifications and board composition relate to innovation outcomes. Results / Findings: The results indicate that CEOs with educational backgrounds in science, technology, engineering, and mathematics (STEM) fields have a significantly positive effect on fintech innovation. Conversely, CEOs with non-STEM educational backgrounds tend to have a negative impact. Furthermore, board diversity is found to positively influence corporate innovation, suggesting that diverse boards enhance strategic decision-making by providing varied perspectives and support to the CEO, particularly in investment-related decisions. Conclusion: These findings contribute to the growing literature on corporate governance and innovation in emerging markets, highlighting the importance of executive qualifications and inclusive leadership structures in fostering innovation in the fintech sector.